Bureaucracy conflicts in border areas: study on conflict between civilian state apparatus and regent in morotai island regency - Latief, Fandi Hi.; Pora, Rasid; Ka’abah, Sri; Wance, Marno (International research journal of management, IT and social sciences, 2021)
Regional bureaucratic conflicts are often caused by regional heads' failure to express the concept of regional bureaucratic development and appear to be political, followed by the regional authorities' egocentrism, causing conflicts for the provincial government's technical implementers (in this case, Civilian State Apparatus. This series of matches has drained energy, costs, and energy for Civilian State Apparatus has been highlighted so that the spirit of bureaucratic reform is highlighted not running optimally. The results of the study show that the conflict begins with the regional head's policy regarding a system of rotation/transfer of positions that are not based on employment regulations, the application of immeasurable reward and punishment, the obligation to take credit, buy a house, and buy a vehicle for state civil apparatus with guaranteed Regional Performance Allowances. Following the position (not having a legal basis) Decree of Promotion for state civil apparatus as much as 611 (3 (three periods of promotion) and the imposition of sanctions for the Acting Regional Secretary of Morotai Island Regency in the form of a Warning Letter for not receiving allowances until an unspecified time limit.